Practice of Physical Activity through Active Video Games in Addressing Obesity in Pediatric Ages - Brian Johan Bustos Viviescas; Carlos Enrique García Yerena; Carlos Alberto Romero Cuestas (Revista Finlay)
The increase in obesity in the world demands a strategic plan aimed at its prevention in the immediate, medium and long term, given that children who present with obesity from an early age tend to maintain this state in subsequent periods of their lives, which leads to acquiring other so-called non-communicable diseases. Advanced studies have identified strategies based on the development of technological proposals that contribute to the promotion of physical activity through active games for children. These proposals constitute postmodern alternatives that motivate a change in sedentary behaviors to consolidate healthy lifestyle habits. It is necessary to implement programs aimed at preventing obesity in pediatric ages, mediated by active video games as educational alternatives that promote the reduction of periods of sedentary lifestyle and the control of chronic non-communicable diseases.